Management of Thyroid Nodules and Differentiated Thyroid Cancer : A Practical Guide - Roman, Sanziana A.; Sosa, Julie Ann; Solórzano, Carmen C. (Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive, state-of-the art review of this field, and will serve as a valuable resource for clinicians and researchers with an interest in the management of thyroid nodules and cancer, including both surgeons and endocrinologists. The book reviews new data about risk factors for nodular disease and cancer, details the management of toxic and non-toxic benign thyroid nodular disease, discusses controversies in the management of indeterminate thyroid nodules and cancer, and reviews the latest data on use of molecular testing for diagnosis and prognosis. Lastly, the book reviews the management of difficult-to-treat thyroid cancers. Management of Thyroid Nodules and Differentiated Thyroid Cancer: A Practical Guide will serve as a useful resource for physicians and researchers dealing with, and interested in thyroid nodular disease and cancer. It will provide a concise yet comprehensive summary of the current status of the field that will help guide patient management and stimulate investigative efforts. All chapters are written by experts in their fields and include the most up to date scientific and clinical information.
Keywords: Medicine.; Endocrinology.; Surgery.; Surgical oncology.; elektronické knihy; electronic books